IMPACT OF ONLINE RETAIL MARKET ON CONSUMER ELECTRONICS TRADERS: AN ANALYTICAL STUDY WITH SPECIAL REFERENCE TO NAGPUR CITY - Agrawal, Shraddha G.; M.D.Gulhane (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The expanding online retail sector possesses substantial influence on consumer electronics traders operating in Nagpur and similar cities. Traditional retailers continue to battle three main issues because consumers increasingly choose e-commerce options: decreased sales numbers, narrow profit margins and more aggressive market pricing. The research examines how online retail shapes consumer electronics traders operating in Nagpur City by studying both behavioral changes among consumers and business results and market competition and trader response strategies. A total of 196 traders answered a structured questionnaire which went through Factor Analysis and ANOVA statistical processing. E-commerce platforms force most traders to experience lower sales revenue because they provide customers with discounts and easy returns as well as transparent pricing. The shopping habits of consumers have changed because customers browse items in physical stores but they choose to purchase products online. Business traders respond to these difficulties through digital marketing initiatives as well as custom service approaches and online sales channels. Many organizations face barriers to implementing technology because financial limitations together with practical operation challenges emerge as obstacles. Consumer choices depend heavily on their trust level together with convenience factors and the range of products available according to the findings of this research. The analysis supports implementing dual business structures and improving customer relationships combined with social media-based promotional efforts. These findings supply crucial knowledge that helps policymakers together with business owners and academic community develop sustainable growth approaches among the current e-commerce dominance.